Fireball and flame venting comparisons: Test data, CFD simulations, and industry standard prediction. (July 2022) - Diakow, Peter A.; Thomas, J. Kelly; Vivanco, Emiliano; Rodriguez, Oscar
Abstract: Baker Engineering and Risk Consultants, Inc. (BakerRisk®) has performed vented deflagration testing of congested enclosures over a range of configurations, congestion levels, and fuels. This paper provides a comparison of the measured flame jetting distances to predictions made applying standard methods commonly used to calculate the associated hazard zone. These methods include the National Fire Protection Association Standard on Explosion Protection by Deflagration Venting (NFPA 68 (National Fire Protection Association, 2018, )), the British Standard's Gas Explosion Venting Protective Systems (EN 14994 (British Standard EN 14994, 2007)), and a computational fluid dynamics (CFD) analysis. Nine test series were carried out using BakerRisk's Deflagration Load Generator (DLG) test rig. The DLG is a rectangular steel enclosure measuring 48-feet wide × 24-feet deep × 12-feet tall, yielding a total volume of 13, 800 ft 3 (391 m 3 ), and is enclosed by three solid steel walls, a roof, and floor. The rig vents through one of the long walls (i.e., 48-foot × 12-foot). The venting face was sealed with a 6-mil (0.15 mm) thick plastic vapor barrier for these tests to allow for the formation of the desired fuel air-mixture throughout the rig. Both slightly hyper-stoichiometric propane and lean hydrogen mixtures have been tested in the DLG. Congestion was provided by an array of vertical cylinders. A range of congestion levels and fill fractions were tested. DLG testing was performed with and without vent panels present. Flame jetting distances from the venting face of the DLG were measured using high-speed video. Flame jetting distances were predicted using the Fireball Dimensions calculation from NFPA 68 and the Flame Effects calculation from EN 14994. Blind (i.e., pre-test) simulations were also performed using the FLACS CFD code (Gexcon, 2014). The flame jetting distance in the CFD simulation was determined as the horizontal distance from the DLG vent to the location where the gas temperature dropped below a specified value; the predicted distance for the fuel concentration to drop below half the lower flammability limit (LFL) was also evaluated to assess jetting distance. Highlights: Large-scale vented deflagration testing was conducted for a congested enclosure. The maximum flame jetting distance from the venting surface was measured. Measurements were compared to predictive methods. The predictive methods were generally conservative compared to the measured values.